Prediksi Kandungan Pati Pepaya IPB9 Selama Penyimpanan dengan Spektroskopinir - Nur Arifiya (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
The parameters of ripe papaya quality consisting of starch content, total soluble solid and water content must be measured by conductinga time-consuming and destructivelychemical analysis. NIR spectroscopy isa non-destructive, accurate, fast methodthat can substitute the such chemical analysis. This study aims to predict starch content, total soluble solid, and water content using NIR spectroscopy. 60 pieces ofpapaya of IPB 9 varietyat the part of top, middle, and bottom was measured with 3 replications. Starch content can be well predicted by NIR spectroscopy with pre-treatment of combination between msc and dg1, as indicated by the model generated by the R, SEC, SEP, CV, and RPD of 0.90, 0.17% 0.16%, 10.95%, and 2.15 respectively. Total soluble solid can bewell predicted by NIR spectroscopy with pre-treatment msc R, SEC, SEP, CV, and RPD, as indicated by 0.90, 0.124%, 0123%, 4.85%, and 2.27 respectively. Similarly, the water content can be well predicted by NIR spectroscopy with pre-treatment dg1 R, SEC, SEP, CV, and RPD, as indicated by 0.84, 0.03%,0.04%, 0.43%, and 1.85 respectively